Pengaruh Environmental Performance Terhadap Kinerja Maqashid Syariah Index Dengan Size Perusahaan Sebagai Variabel Moderasi - Sri Hanifah; Ekawati, Evi; Malik, Anas (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to examine the influence of environmental performance on the Maqashid Shariah Index (MSI), with firm size serving as a moderating variable. The research is centered on food and beverage companies listed on the Indonesia Sharia Stock Index (ISSI) between 2019 and 2023. This sector was selected due to its notable environmental impact and its vital role in supporting ethical and halal consumption in accordance with Islamic principles.Methods: A quantitative method was employed, utilizing secondary data sourced from annual reports, sustainability reports, and environmental performance ratings published through the PROPER program. The analysis employed Moderated Regression Analysis (MRA) to evaluate both the direct and interaction effects among the variables.Results: The findings reveal that environmental performance has a significant and positive impact on the Maqashid Shariah Index. Furthermore, firm size enhances this relationship, indicating that larger companies that implement strong environmental practices tend to achieve higher MSI scores. This suggests that greater resource availability and organizational visibility contribute to more sustainable outcomes and alignment with Sharia objectives. These results underscore the importance of incorporating environmental responsibility into sharia-compliant business models. This study contributes to the development of Islamic accounting by illustrating how environmental engagement and firm scale interact to support the realization of maqashid shariah goals, providing practical insights for governance and policy design in sharia-based corporate frameworks. Keywords: Keywords: Environmental Performance, Maqashid Shariah Index, Food And Beverage, ISSI, Firm Size